2013
DOI: 10.1029/2012wr012570
|View full text |Cite
|
Sign up to set email alerts
|

A spatial and nonstationary model for the frequency of extreme rainfall events

Abstract: [1] Changes in the properties of extreme rainfall events have been observed worldwide. In relation to the discussion of ongoing climatic changes, it is of high importance to attribute these changes to known sources of climate variability. Focusing on spatial and temporal changes in the frequency of extreme rainfall events, a statistical model is tested for this purpose. The model is built on the theory of generalized linear models and uses Poisson regression solved by generalized estimation equations. Spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 45 publications
1
42
0
Order By: Relevance
“…In the analysis of extreme precipitation in Belgium, Ntegeka and Willems (2008) found multi-decadal oscillations that can be partly explained by atmospheric circulation patterns, and a departure from this oscillation with trends towards more extreme precipitation in recent decades may be an indication of climate change. Gregersen et al (2013b) showed that the temporal variations in the frequency of extreme rainfall events in Denmark can be partly explained by atmospheric circulation patterns, average summer precipitation, and average summer temperature.…”
Section: Key Findingsmentioning
confidence: 99%
“…In the analysis of extreme precipitation in Belgium, Ntegeka and Willems (2008) found multi-decadal oscillations that can be partly explained by atmospheric circulation patterns, and a departure from this oscillation with trends towards more extreme precipitation in recent decades may be an indication of climate change. Gregersen et al (2013b) showed that the temporal variations in the frequency of extreme rainfall events in Denmark can be partly explained by atmospheric circulation patterns, average summer precipitation, and average summer temperature.…”
Section: Key Findingsmentioning
confidence: 99%
“…Willems (2013) concluded that a higher degree of explanation is obtained if the index is estimated from SLPD between Gibraltar and Scandinavia. Gregersen et al (2013a) found a correlation between the frequency of heavy rainfall events and the East Atlantic (EA) pattern, which is the second most prominent mode of SLP variability over the North Atlantic (NOAA 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…Both Min et al (2011) and Westra et al (2013) concluded that a statistically significant increase in the annual maximum daily precipitation can be detected on a global basis. For Northern and Central Europe a number of recent studies exists for various regions; Belgium (Ntegeka and Willems 2008), Czech Republic (Kysely 2009), Denmark (Gregersen et al 2013a), Germany/Poland (Lupikasza et al 2011), Sweden (Bengtsson andRana 2013) and UK (Rodda et al 2010). Depending on season, region within the country and analysed indices, they all detect changes in heavy rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…However, no spatial explanatory variable was used. On the other hand, Gregersen et al [24] used regional spatial explanatory variables to handle spatial correlation in addition to using large-scale indices to explain temporal variability of the frequencies of rainfall extremes over Denmark and estimated the contribution of each explanatory variables (covariates) toward explaining spatial or temporal variation using a unregularized multivariate regression technique. While we borrow their approach of using regional-scale spatial variables to explain the spatial variability of the rainfall frequencies, our goal is to use as many variables as possible-both atmospheric variables at multiple spatial scales and large-scale climate indicesto use as potential covariates to explain any possible variability in extreme frequencies.…”
mentioning
confidence: 99%